Septate uterus with cervical duplication and a longitudinal vaginal septum: an unclassified mullerian anomaly - Mangla, Ruchika; Kaur, Tajinder; Pathak, Nayana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Uterine anomalies are the result of disturbances in the development, formation or fusion of the mullerian ducts during foetal life with an incidence of 0.001%-10% in general population. These patients most often present with amenorrhoea, dysmenorrhoea, dyspareunia and infertility. Women with these anomalies are more prone to poor foetal outcomes such as first trimester losses or preterm labour. We report a case of a 35 years old female with septate uterus with cervical duplication and a longitudinal vaginal septum. Diagnosis was obtained by physical examination, ultrasound imaging, hysterosalphingography and magnetic resonance imaging and hysterolaproscopy. The clinical presentation of such a case & surgical options available were studied, and the excision of the vaginal septum was done. This case of congenital uterine anomaly does not fit into the current classification system of mullerian anomalies by American fertility society, which is based on the traditional caudal to cranial, unidirectional developmental pattern. This strongly indicates the possibility of an alternative mechanism of mullerian development.